Inhibition of p53 attenuates ischemic stress-induced activation of astrocytes. Issue 14 (30th September 2015) - Ahn, Kee-Chan; MacKenzie, Erin M.; Learman, Cameron R.; Hall, Tia C.; Weaver, Charles L.; Dunbar, Gary L.; Song, Mee-Sook
<x xml:space="preserve">Abstract</x> In cerebral ischemia, studies of cell death have focused primarily on neurons, but recent work indicates that ischemia also causes damage to astrocytes. Activation of astrocytes is a typical brain response to stress stimuli and is evidenced by changes in cellular function and morphology, as well as upregulation of glial fibrillary acidic protein. The tumor-suppressor transcription factor p53 has recently been implicated as a mediator of ischemia-induced neuronal death, but very little is known about its role in the activation or the death of astrocytes. The present study investigated the role of p53 in astrocyte and neuronal toxicity using in-vitro and in-vivo ischemic stroke models. We showed that p53 is activated in ischemic brains and in oxygen–glucose deprivation (OGD)-induced cell death in neurons and astrocytes. Inhibition of p53 activity using either pifithrin-α or small interference RNA interference reduced OGD-induced cell death and pifithrin-α reversed OGD-induced impairment of glutamate uptake in astrocytes, suggesting that p53 might play a key role in mediating neurotoxicity and gliotoxicity in ischemic brain injury. This study shows that p53 is activated in astrocytes during ischemia and that inhibition of the activity of this molecule prevents not only OGD-induced neuronal and astrocytic death but also astrocyte activation and impaired glutamate uptake. These findings suggest that p53 may be a valuable therapeutic target in ischemic brain injury.